Repurposing the Native Type I-F CRISPR-Cas System in Pseudomonas aeruginosa for Genome Editing - Zeling Xu; Yanran Li; Aixin Yan (STAR Protocols, 2020)
SUMMARY: Repurposing the broadly distributed native CRISPR-Cas systems in prokaryotes for genome editing is emerging as a new strategy for genetic manipulations. We recently reported the establishment of a single plasmid-mediated, one-step genome-editing technique in a multidrug-resistant genotype of the opportunistic pathogen Pseudomonas aeruginosa by harnessing its endogenous type I-F CRISPR-Cas system. The platform is readily applicable in additional type I-F CRISPR-containing clinical and environmental P. aeruginosa isolates. Herein, we provide the detailed protocol for the methodology.For complete details on the establishment and exploitation of this protocol, please refer to Xu et al. (2019).